Implementasi Website e-Commerce Berbasis CMS (Content Management System) pada Toko Olahraga XYZ - Jeremy Jonathan; Ikhsan Rahdiana; Firdha Aprilyani (Jurnal Sistem Informasi, 2023)
Abstract— Technological developments require businesses to be able to prioritize fast service, increase productivity, and convenience and create superior products. By selling and buying products via the internet, it will make it easier for people to access e-commerce websites effectively and efficiently and increase store sales. The problems that occur in Sports Stores XYZ are that there is no system to inform product details, product prices, product sizes, and product stock so that customers run out of items they want to buy, lack of maximum sales promotion, no reports for the best-selling products, lack of maximum results in searching sales report data. This research method builds and designs E-commerce with a WordPress content management system (CMS), develops a B2C (Business-to-Customer) E-commerce model, discusses making product catalogs, ordering products, product transactions, and confirming payments, payment is done by transfer between banks and then the shop will validate if the buyer has confirmed the payment. This research resulted in the availability of product catalog, cart, and checkout features on the E-commerce system, the coupon feature and the sales report feature, and best-selling products. Keywords — E-commerce, Internet, CMS, Wordpress, B2C.